2008
DOI: 10.1111/j.1600-0897.2008.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Poly‐Immunoglobulin Receptor‐Mediated Transport of IgA into the Male Genital Tract is Important for Clearance of Chlamydia muridarum Infection

Abstract: These findings indicate that a Chlamydia vaccine that induces neutralizing IgA in the prostate will aid in the protection against infection in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The role of IgA in chlamydial infections remains controversial. Indeed, while the absence of IgA in IgA-deficient mice seems to have no effect on clearance of primary or secondary infections, other studies have reported the effect of anti-MOMP IgA (from either vaccination with a MOMP vaccine or adoptive transfer) on reducing chlamydial infections in mice [46, 47, 51]. Thus, although our data supported a role for IgA in lowering chlamydial burden in koalas, further experiments are required to fully elucidate the role of mucosal immunity in chlamydial infections.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IgA in chlamydial infections remains controversial. Indeed, while the absence of IgA in IgA-deficient mice seems to have no effect on clearance of primary or secondary infections, other studies have reported the effect of anti-MOMP IgA (from either vaccination with a MOMP vaccine or adoptive transfer) on reducing chlamydial infections in mice [46, 47, 51]. Thus, although our data supported a role for IgA in lowering chlamydial burden in koalas, further experiments are required to fully elucidate the role of mucosal immunity in chlamydial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we reported that male guinea pigs which were depleted of B cells by cyclophosphamide treatment, leaving cell-mediated immunity intact, had a longer course of infection with increased pathology (26). Moreover, Cunningham and colleagues recently demonstrated that polyimmunoglobulin receptor-mediated transport of IgA played an important role in the clearance of infection from the genital tracts of male mice (2). In female guinea pigs, humoral immunity is essential for the recovery of chlamydial genital infection (25), and immune serumderived antibody contributed to protection against a genital tract infection (21).…”
Section: Discussionmentioning
confidence: 97%
“…We surmise that the induction of IgA at mucosal sites is also important for protection against chlamydial infection in male koalas. Indeed, in the murine model higher levels of IgA in the prostatic fluid correlates with a reduction of Chlamydia infection in vitro and in vivo [32]. However, reagents to measure the induction of IgA at mucosal sites are not yet available for the koala.…”
Section: Discussionmentioning
confidence: 98%